Stress and organs and tissues procurement for transplantion: the experience of nurses - a dissertation abstract - Aparecida de Jesus Guarino; Estela RF Bianchi (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2006)
ABSTRACT The purpose of this study is to know and compare the stressors and the health condition of the nurses whose job is in the organ and tissue procurement transplantation. Seventeen nurses comprised the sample and they were from three Organs and Tissues Procurement Organizations (OPO), a governmental organization, in São Paulo- Brazil. Participants filled out two questionnaires. Job stress was assessed with the 39-item scale. It is a Likert-type scale with 1 - 7 response options, "1" indicating no stressed and "7" indicating a strong stressed with the item. A higher score on the scale indicated a higher degree of job stress. Health problems were assessed by 54- item questionnaire, with "1" indicating no problem and "3" indicating frequent problem. Stressors were classified as interpersonal relationship, nursing care, unit administration, knowledge and abilities; self perception and work conditions. The data from health condition could be: 0 to 42 as "good" health, 44 to 87 as "regular" and 88 to 130 as "bad". Fisher and Kruskal-Wallis correlation tests were used to analyse the data. Cronbach's alpha coefficients assessing internal consistency were 0.9040. Questionnaires were distributed and collected by author, with anonymity being assured for each respondent. The majority of the respondents were female (51.8%), from 21 to 30 years old (70.6%) and had from 1 to 5 years as transplantation nurse (76.5%). The findings seemed to indicate that nurses were stressed. Stressors classified as "self perception" were the most stressed, and the range was from 5.06 to 7.0 and the less stressed items were approached by "interpersonal relationship" with the range of 3.55. Associations statistically significant were observed: female and "work conditions" (p= 0.024) that means that woman had more stress than man; more than 5 years after completed education had more stress and "self perception" (p= 0.002); and who worked more than 5 years in OPO and "self perception" (p= 0.011). Although those results as stressed nurses, their health condition was considered as "good" (76.5%). There was no significant correlation between stress level and health condition. Nurses and hospitals administration need to be more aware of stressors that influence nurses as organ and tissue procurement transplantation. Stress inoculation training which teaches nurses appropriate coping skills could be implemented. Key words: nurses job; nursing; transplantation